Association of CCND1 and HR-HPV16/18 in endometrial tumors - Mohammed Ali, Saad Hasan (Iraqi Journal of Cancer and Medical Genetics, 2015)
Background: A number of reports have demonstrated the presence of HPV in endometrial adenocarcinomas(ECs) . alterations in Cyclin D1(CCND1) gene expression has been reported in ECs and the integration of human papilloma virus (HPV)could alter the level of gene expression of CCND1. Methodology: This study has used in situ hybridization to localized HR-HPV16/18 in tissue specimens from 70 hysterectomized patients diagnosed with malignant endometrial tumors (30 cases), non-malignant endometrial tumors (25 cases),and 15 cases as control tissues groups. Also the study has enrolled detection the gene expression of CCND1 using Immunohistochemistry. Results:In the cancer sites malignant endometrial tumors group, HR-HPV16/18 was detected in 10 cases(33.3%) ,and in 5 cases (20%) non-malignant endometrial tumors ,and 4 cases (26.7%)of control tissues group. Most HPV16/18 infections have Punctate DNA pattern .The results of moleculare detection of CCND1 revealed 13(43.3%) in malignant endometrial tumor 8(32%) non-malignant endometrial tumor and 6(40%) in control groups. The significant correlation between CCND1 expression and HR-HPV16/18 infection was reported only in malignant endometrial tumors groups. Conclusions: HR-HPV16/18 may be associated with initiation of endometrial carcinogenesis events as well as play a role in the progression of such malignant tumors.CCND1 could have sharing in early events of tumorgenesis in endometrial carcinoma and a significant correlations of CCND1 expressions with HPV infection was observed among malignant endometrial tumor.